2009
DOI: 10.1007/s00125-009-1592-4
|View full text |Cite
|
Sign up to set email alerts
|

The gait and balance of patients with diabetes can be improved: a randomised controlled trial

Abstract: Aims/hypothesisGait characteristics and balance are altered in diabetic patients. Little is known about possible treatment strategies. This study evaluates the effect of a specific training programme on gait and balance of diabetic patients.MethodsThis was a randomised controlled trial (n = 71) with an intervention (n = 35) and control group (n = 36). The intervention consisted of physiotherapeutic group training including gait and balance exercises with function-orientated strengthening (twice weekly over 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
259
0
16

Year Published

2010
2010
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 269 publications
(281 citation statements)
references
References 41 publications
6
259
0
16
Order By: Relevance
“…While some well-performed studies have described the effects of balance training on patients with DN [13,[22][23][24], few investigations have attempted to mitigate the context-specific postural instability problem in this population [24][25]. Some studies, however, have reported on the correlation between balance training and visual external feedback.…”
Section: Introductionmentioning
confidence: 99%
“…While some well-performed studies have described the effects of balance training on patients with DN [13,[22][23][24], few investigations have attempted to mitigate the context-specific postural instability problem in this population [24][25]. Some studies, however, have reported on the correlation between balance training and visual external feedback.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown velocity increases in senior citizens as a result of balance training. Allet et al 32) reported that task-oriented balance exercises for 12 weeks resulted in an 11.6% improvement in velocity, and Hill et al 33) reported that 6 months of multi-factorial interventions with tasks increased velocity by 11.5% in elderly people. Although the present study included people of different ages, and has limitations on directly comparing gait changes, balance training with cognitive tasks is considered to enhance mobility.…”
Section: Discussionmentioning
confidence: 99%
“…Gait could be affected in three possible levels, peripheral secondary myopathy, DPN and DAN, spinal cord to brainstem resulting from small vessel strokes causing loss of sensory information and coordination, and cortical/subcortical lesions from DM related strokes, neurodegenerative diseases and small vessel disease causing higher level gait apraxia [62]. Specific advice on lifestyle choices as well as training has been shown to improve reaction time, postural balance and gait speed [63]. Directed physical therapy to the ankle to help reduce rollovers and improve stability [64].…”
Section: Rehabilitationmentioning
confidence: 99%